Papal Indulgences and the Conversion of Schismatics in Late Medieval Transylvania (c.1350-c.1450) - Popovici, Teodora (Studies in church history, 2025)
This article explores the self-representations of marginality found in the indulgence petitions addressed by Transylvanian supplicants to the papal chancery during the fourteenth and fifteenth centuries. As one of Hungary's border provinces, Transylvania was located on the eastern frontier of late medieval Latin Christendom. Although Transylvanian Catholics often expressed a sense of marginality in their petitions to the pope, this sentiment was not primarily defined by the petitioners' distance to the Apostolic see; rather, it was described in relation to the Greek Orthodox Christians in Transylvania and, later, to the approaching Ottoman Turks. To illustrate this point, the article presents three case studies of indulgence petitions submitted by Transylvanian supplicants between 1350 and 1450, highlighting how the petitioners' discourse about marginality changed over the course of this period. In addition, this article emphasizes the role attributed by petitioners to papal indulgences in converting the "schismatics" in Transylvania to the Latin faith.